Differential Larval Toxicity and Oviposition Altering Activity of Some Indigenous Plant Extracts against Dengue and Chikungunya Vector Aedes albopictus. - Ruchi Yadav; Varun Tyagi; Sachin N Tikar; Ajay K Sharma; Murlidhar J Mendki; Ashok K Jain; Devanathan Sukumaran (Tehran University of Medical Sciences, 2014)
Background: Mosquitoes are well known as vectors of several disease causing pathogens. The extensive use of synthetic insecticides in the mosquito control strategies resulted to the development of pesticide resistance and fos- tered environmental deterioration. Hence in recent years plants become alternative source of mosquito control agents. The present study assessed the larvicidal and oviposition altering activity of six different plants species- Alstonia scholaris, Callistemon viminalis, Hyptis suaveolens, Malvastrum coromandelianum, Prosopis juliflora, Vernonia cinerea against Aedes albopictus mosquito in laboratory. Methods: Leaf extracts of all the six plants species in five different solvents of various polarities were used in the range of 20-400ppm for larval bioassay and 50,100 and 200ppm for cage bioassay (for the study of oviposition be- havior) against Ae. albopictus. The larval mortality data were recorded after 24 h and subjected to Probit analysis to determine the lethal concentrations (LC50), while OAI (Oviposition activity index) was calculated for oviposition altering activity of the plant extracts. Results: Vernonia cinerea extract in acetone and C. viminalis extract in isopropanol were highly effective against Aedes albopictus larvae with LC50 value 64.57, 71.34ppm respectively. Acetone extract of P.  juliflora found to be strong oviposition-deterrent which inhibited >2 fold egg laying (OAI-0.466) at 100ppm. Conclusion: Vernonia cinerea and C. viminallis leaf extracts have the potential to be used as larvicide and P.juliflora as an oviposition-deterrent for the control of Ae. albopictus mosquito.